Assisted Living Facilities for People with Disabilities - Examples of Good Practices - Olszewski, Mikołaj (Studia Oeconomica Posnaniensia, 2019)
The author analyzes solutions in the field of assisted housing for persons with disabilities and discusses some examples of good practices in the creating and running of sheltered housing or assisted living facilities in Poland by municipalities, social welfare units together with (TBS-social housing society) and non-governmental entities. The author also refers to assisted living facilities in France, pointing to the possibility of using these solutions in Poland as part of social housing. The method used in the article is an analysis of secondary sources: ministerial reports, the substantive reports of institutions, NGO's running of assisted housing facilities, and legal acts, as well as literature on the subject and a review of good practices from Poland and France. The author recommends in the conclusions the use of TBS (social housing society) for the construction of assisted living facilities and sheltered housing, while implementing art. 19 UN Convention on the Rights of Persons with Disabilities on promoting the independent life of people with disabilities.